Peran Teknologi Informasi dalam Transformasi di Industri Perkapalan - Alfito Darryl Ramadhan; Rafa Mutiara Negara; Reiza Wienda Azzahra; Bagus Rahmadi; Denny Oktavina Radianto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Management transformation in the shipping industry has become increasingly important with the advancement of information technology. This research aims to analyze the role of information technology in management transformation in the shipping industry. Through a literature review approach, this study explores the use of information technology in enhancing operational efficiency, facilitating faster decision-making, and improving company competitiveness. The main findings indicate that information technology has been a key driver in management transformation, with the adoption of integrated logistics management systems and real-time ship monitoring. However, challenges such as infrastructure complexity, data security issues, and resource constraints are also identified in the implementation of information technology. Effective mitigation strategies are needed to address these challenges. This study also highlights the importance of collaboration and partnerships in the transformation of the shipping industry. Thus, this research provides a comprehensive understanding of the role of information technology in management transformation in the shipping industry, while highlighting the challenges faced and their practical implications.